Decreased daytime light intensity at nonwindow hospital beds: Comparisons with light intensity at window hospital beds and light exposure in nonhospitalized elderly individuals. (4th May 2018) - Iwamoto, Junko; Obayashi, Kenji; Kobayashi, Miwa; Kotsuji, Toshimichi; Matsui, Rie; Ito, Kyoko; Yoshida, Osamu; Kurumatani, Norio; Saeki, Keigo
ABSTRACT: Light is crucial for the synchronization of internal biological rhythms with environmental rhythms. Hospitalization causes a range of unfavorable medical conditions, including delirium, sleep disturbances, depressed mood, and increased fall, especially in elderly people. The hospital room environment contributes significantly to patients' circadian physiology and behavior; however, few studies have evaluated light intensity in hospital settings. In this study, bedside light intensity during the daytime (6:00–21:00) was measured at 1-min intervals using a light meter on 4869 bed-days at the Inabe General Hospital in Mie, Japan (latitude 35°N), for approximately 1 month in each season. Daytime light exposure in home settings was measured in nonhospitalized elderly individuals ( n  = 1113) for two consecutive days at 1-min intervals using a wrist light meter. Median daytime light intensities at window and nonwindow hospital beds were 327.9 lux [interquartile range (IQR), 261.5–378.4] and 118.4 lux (IQR, 100.6–142.9), respectively, and daytime light intensity measured in nonhospitalized elderly individuals was 337.3 lux (IQR, 165.5–722.7). Compared with data in nonhospitalized elderly individuals, nonwindow beds were exposed to significantly lower daytime light intensity ( p  < 0.001), whereas window beds were exposed to similar daytime light intensity to that of home settings ( p  = 1.00). These results were consistent regardless of seasons (spring, summer, fall, and winter) or room directions (north vs. south facing). The lowest median daytime light intensity was observed at nonwindow beds in north-facing rooms during the winter (84.8 lux; IQR, 76.0–95.8). Further studies evaluating the incidence of in-hospital outcomes between patients hospitalized in window and nonwindow beds are needed.